Style Effects in the Cross-Section of Stock Returns - TEO, Melvyn (Institutional Knowledge at Singapore Management University, 2004)
Using CRSP stock and mutual fund data, we find strong evidence for reversals at the style level (e.g., large value, small growth, etc.). There are significant excess and risk-adjusted returns for stocks in styles characterized by the worst past returns and net inflows. We also find evidence for momentum and positive feedback trading at the style level. These value and momentum effects are driven neither by fundamental risk nor by stock-level reversals and momentum. Taken together, the results are consistent with the style-level positive feedback trading model of Barberis and Shleifer (2003).